PENGARUH JIWA KEWIRAUSAHAAN DAN KREATIVITAS TERHADAP KEBERHASILAN USAHA PADA UKM PENJAHIT DI KECAMATAN BATURAJA TIMUR KABUPATEN OGAN KOMERING ULU - Rr Dimas Veronica Priharti; Tati Herlina; Vira Annisa (STIE DWI SAKTI BATURAJA, 2022)
The analytical tool used in this research is multiple linear regression. The purpose of this research is to determine the influence of entrepreneurship and creativity on business success in tailoring SMEs in Baturaja Timur Sub-District, Ogan Komering Ulu Regency. Based on the results of the analysis and discussion that has been carried out, simultaneously that entrepreneurship and creativity have an influence on the success of the business of tailoring SMEs in Baturaja Timur Sub-District, Ogan Komering Ulu Regency. Partially it is known that the t-count of entrepreneurship (X1) is 0.645 < t-table of 2.034, then the entrepreneurship (X1) has no influence on business success (Y), the t-count of creativity (X2) is 2.848 > the t-table is 2.034 then creativity (X2) has a significant influence on business success (Y). The results of data processing the coefficient of determination R Square is 0.198. It means that the percentage contribution of the influence of entrepreneurship and creativity on business success is 19.8%, while the remaining 80.2% is influenced by other variables outside the variables discussed in this researcj such as innovation, ability, commitment.